Sistem Penunjang Keputusan Penerima Bantuan Pinjaman Modal Usaha Kecil Menengah Menggunakan Metode SMART Berbasis Web - Raina, Raina; Dadan Nugraha (Scientific Exploration: Journal of Indonesian Academic Research, 2023)
The revolving business capital assistance program is a program of village-owned enterprises (BUMDes) in Tirtawangunan Village which aims to overcome economic problems within the Tirtawangunan Village. This program helps community developing businesses for Businessman. The selection process for business capital loan recipients is still manual and there is no calculations which causes problems in the process of verifying the eligibility of beneficiaries. The research was conducted using the SMART method with the criteria used in the calculation process, namely income, Responsibility for Children, level of occupancy eligibility, letters of recommendation. To optimize the selection process for loan recipients, a computer-based system called a decision support system was developed. The system development method used is waterfall. This decision support system was created in web form using PHP as the programming language and MySQL as the database. SMART is a multi-criteria decision-making technique based on the theory that each alternative consists of a number of criteria having a weight of how important it is compared to other criteria. The system built can provide recommendations from the largest to the smallest values. For the UAT resut it shows that 20 people, an average value of 93.4% was obtained. In conclusion this decision support system can be accepted by the user.